(untitled) (Archive of Conferences, 2022)
This story reveals the fate of a man who endured the trials of life. He too had the right to live well and to be fed by the love of his parents. But the trials of destiny deprived him of these things. But in time, as the moon was said to be fifteen bright and fifteen dark, a bright and bright future awaited him. ’In those days, instead of being a pillar, he was treated as an enemy. Nasibjon was also a man who understood what his relatives were like. He did not receive any love or help from any of his relatives during his life. This is also a test of destiny